Associations between physical fitness and executive functions in 10–13 year male children in Saudi Arabia - Alghamdi, Rana Jamaan; Alotaibi, Salem; Aljuhani, Osama; Alkahtani, Shaea (Frontiers in Psychology, 2025)
ObjectivesThe aim of the present study was investigating the associations between physical fitness and executive function tasks in children aged 10–13 years, with a particular focus on the contribution of physical fitness to working memory.FindingsThe findings reported significant correlations between the N-Back task (a measure of working memory) and all three physical fitness tasks: grip strength, long jump, and shuttle run. Additionally, the Flanker task (assessing selective attention) was correlated only with the shuttle run task. However, no significant correlation was found between the Stroop task (measuring inhibition control) and the physical fitness tests. Regression analyses further demonstrated that physical fitness tasks significantly contributed to working memory performance, independent of age and BMI.ContributionsThese findings emphasize the importance of incorporating diverse physical activities in children’s routines to support both physical and cognitive development, particularly in enhancing working memory, which is critical for academic achievement. From an educational and policy standpoint, integrating targeted fitness programs into school curricula may foster both physical health and cognitive development. Consequently, this study underscores the need for holistic approaches that combine physical and cognitive interventions, ultimately enhancing overall development and academic performance in schoolchildren. Hence, this study underscores the need for holistic educational interventions that integrate physical fitness with cognitive development.